2014
DOI: 10.3329/jbau.v11i1.18207
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stomatal characteristics on yield and yield attributes of rice

Abstract: Stomatal distribution is found to be an important trait of rice cultivars for increasing yield. A total of six rice cultivars, three from each of inbred and hybrid cultivars, were used to study stomatal distribution on the leaf epidermis and its influence on yield and yield attributing characters of rice during the Boro season. The hybrid cultivars exhibited superiority in respect of number of stomata, length and breadth of stomatal apparatus. They also produced longer panicle, higher number of filled grains p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
(10 reference statements)
2
8
0
Order By: Relevance
“…Various studies have demonstrated the role of stomata in biomass accumulation and crop yield determination. Sarwar et al 24 reported a significant and positive correlation of stomatal length, width, and density with the grain yield in rice. Parallel to our study, they demonstrated positive regression plots between yield and stomatal traits.…”
Section: Number Of Internodesmentioning
confidence: 99%
“…Various studies have demonstrated the role of stomata in biomass accumulation and crop yield determination. Sarwar et al 24 reported a significant and positive correlation of stomatal length, width, and density with the grain yield in rice. Parallel to our study, they demonstrated positive regression plots between yield and stomatal traits.…”
Section: Number Of Internodesmentioning
confidence: 99%
“…They also reported that stomatal length is related to specific stomatal conductance which is closely related with leaf photosynthesis, producing higher yield in hybrid cultivars. Hybrid rice cultivars produce higher grain yield, might be due to higher number of large sized stomata causing higher photosynthetic efficacy (Sarwar et al 2013). Recently, Giuliani et al (2011) in rice used Pearson Correlation matrix for trait to trait and suggested that large differences are due to trade off in gas exchange parameters and leaf structural features rather than a single individual trait.…”
Section: Correlationmentioning
confidence: 99%
“…Stoma size is related to specific stomatal conductance which is closely related to leaf photosynthesis leading to higher yield in hybrid cultivars in rice (Ohsuni et al 2007). In similar studies, significant positive correlations between grain yield and number, length and breadth of stomatal apparatus in rice and wheat was shown (Yousufzai et al 2009;Arminian et al 2010;Sarwar et al 2013). These researchers concluded that, number and size of the stomata were directly related with photosynthetic activities and higher photosynthetic activities in turn were related to higher yield.…”
Section: Resultsmentioning
confidence: 68%
“…Although anatomy and the number of stomata in apple, chestnut, walnut, grape, cherry, mahaleb cherry and fig are well documented there is no published paper available on hazelnuts (Aksoy & Mısırlı 1994;Marasalı & Aktekin 2003;Çağlar et al 2004;Gülen et al 2004;Mert et al 2009). Stomatal features have significant effects on certain physiological processes such as photosynthesis, transpiration, plant photosynthetic activities and responses to environmental factors as reported on field crops such as rice and wheat (Ohsinu et al 2007;Yousufzai et al 2009;Arminian et al 2010;Sarwar et al 2013). Significant positive correlations between stomatal features with yield and yield related traits were observed in some of these studies and these relationships were used as criteria in selection of drought resistant and high yielding varieties.…”
Section: Introductionmentioning
confidence: 91%